Single electron transfer events and dynamical heterogeneity in the small protein azurin from Pseudomonas aeruginosa. Issue 3 (4th December 2019) - Pradhan, Biswajit; Engelhard, Christopher; Van Mulken, Sebastiaan; Miao, Xueyan; Canters, Gerard W.; Orrit, Michel
Abstract : Observing electron transfer events in individual azurin molecules, we relate the spread in transfer rates in a unique way to variations in molecular parameters. Abstract : Monitoring the fluorescence of single-dye-labeled azurin molecules, we observed the reaction of azurin with hexacyanoferrate under controlled redox potential yielding data on the timing of individual (forward and backward) electron transfer (ET) events. Change-point analysis of the time traces demonstrates significant fluctuations of ET rates and of mid-point potential E 0 . These fluctuations are a signature of dynamical heterogeneity, here observed on a 14 kDa protein, the smallest to date. By correlating changes in forward and backward reaction rates we found that 6% of the observed change events could be explained by a change in midpoint potential, while for 25% a change of the donor–acceptor coupling could explain the data. The remaining 69% are driven by variations in complex association constants or structural changes that cause forward and back ET rates to vary independently. Thus, the observed spread in individual ET rates could be related in a unique way to variations in molecular parameters. The relevance for the understanding of metabolic processes is briefly discussed.